2020
DOI: 10.1182/blood.2019004719
|View full text |Cite
|
Sign up to set email alerts
|

Correcting β-thalassemia by combined therapies that restrict iron and modulate erythropoietin activity

Abstract: ß-thalassemia intermedia is a disorder characterized by ineffective erythropoiesis (IE), anemia, splenomegaly and systemic iron overload. Novel approaches are being explored based on the modulation of pathways that reduce iron absorption (i.e. using hepcidin activators like Tmprss6-antisense oligonucleotides (ASO)) or increase erythropoiesis (by erythropoietin (EPO) administration or by modulating the ability of transferrin receptor 2 (Tfr2) to control red blood cell (RBC) synthesis). Targeting Tmprss6 mRNA by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 39 publications
6
66
0
Order By: Relevance
“…We do not know if this phenotypic improvement would be sustained over a longer treatment period. Of note, work by Casu et al published during the preparation of this manuscript demonstrate not only a comparable amelioration of the Hbb th3/+ hematological phenotype, but also a similar decrease in splenomegaly using Tmprss6‐ASO with removal of a single Tfr2 allele in the bone marrow of Hbb th3/+ mice 35 …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We do not know if this phenotypic improvement would be sustained over a longer treatment period. Of note, work by Casu et al published during the preparation of this manuscript demonstrate not only a comparable amelioration of the Hbb th3/+ hematological phenotype, but also a similar decrease in splenomegaly using Tmprss6‐ASO with removal of a single Tfr2 allele in the bone marrow of Hbb th3/+ mice 35 …”
Section: Discussionsupporting
confidence: 54%
“…Because we employed the Tfr2 Y245X/Y245X genetic null model we cannot determine if the enhanced effectiveness of the Tmprss6 siRNA treatment requires a loss of functional Tfr2 in the liver, bone marrow, or both tissues. However, it was recently shown by others that loss of functional Tfr2 in bone marrow alone, along with pharmacological iron restriction, is able to ameliorate the Hbb th3/+ phenotype 35 . It may be of interest to confirm that loss of Tfr2 specifically in hepatocytes does not enhance effective erythropoiesis in a thalassemic model under mild iron restriction.…”
Section: Discussionmentioning
confidence: 97%
“…In 2018, Artuso et al found that the bone-marrow specific deletion of Tfr2 moderately lessens the symptoms of β-thalassemia in their Hbb th3/+ mouse model, when combined with an iron restricted diet [ 87 ]. More recently, a study from Casu et al combined Tfr2 knockout with iron depletion by targeting the negative regulator of Hepcidin ( Tmprss6 ) which shows superior correction of anemia in Hbb th3/+ mice [ 88 ]. In both studies, the number of RBCs and the hemoglobin level are increased and iron deposits in the liver, spleen, and kidney are decreased.…”
Section: Transferrin Receptors As Clinical Markers and Therapeuticmentioning
confidence: 99%
“…As iron deprivation seems to ameliorate the symptoms, this is an alternate explanation to consider. These studies in the context of β-thalassemia intermedia have been done with the same mouse models [ 87 , 88 ]. However, varying results have been obtained with Tfr2 knockout depending on the mouse model before [ 10 , 59 , 61 , 62 ], probably partly due to differing basal level of iron [ 63 ].…”
Section: Transferrin Receptors As Clinical Markers and Therapeuticmentioning
confidence: 99%
“…For example, administration of short peptides that mimic the activity of hepcidin have improved ineffective erythropoiesis, anaemia and iron overload in thalassaemic mice 44 . This effect can also be achieved in thalassaemic mice by targeting Tmprss6 mRNA with Tmprss6 antisense oligonucleotides alone or combined with other modalities 45 . Clinical trials have started where exogenous hepcidin mimetics, administered to humans, have been shown to lower transferrin saturation, 46 although the effect in thalassaemia and MDS is not yet known.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%